Analisis Tahapan Keterampilan Pemebelajaran Melalui Praktik Microteaching Pada Mahasiswa di STAI Sulthan Syarif Hasyim Siak Sri Indrapura Riau - Hatta, M; Marzuki, Marzuki; Amin, Muhammad (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
This study aims to see the level of mastery of basic teaching skills of students, especially at the learning planning stage for Islamic Religious Education Study Program Students at STAI Sulthan Syarif Hasyim Siak Sri Indrapura Riau through microteaching activities. The results of the study obtained include: From the results of the presentation of the discussion analysis in this study, the first conclusion can be obtained, semester VI Local A students of the Islamic Religious Education study program at STAI Sulthan Syarif Hasyim Siak Sri Indrapura Riau have carried out 8 aspects of teaching skills for microteaching classes, namely: 1) opening and closing learning skills; 2) questioning skills, 3) providing variation skills, 4) providing reinforcement skills, 5) explaining skills, 6) class management skills, 7) small group management skills, 8) individual and small group management skills. Second, it can be seen that in the skills of opening and closing lessons with an average score of 82.3% with a very good ranking criterion. In the aspect of explaining the average score is 77.5% with good criteria. The aspect of reinforcement got an average score of 85% with very good criteria. The aspect of holding variations got an average score of 73.2% with good criteria. The aspect of managing small groups got a score of 72% with good criteria. The aspect of questioning skills got a score of 78% with good criteria. The aspect of class management got a score of 81% with very good criteria. Finally, the aspect of teaching small groups and individuals got an average score of 76.2 with good criteria. Third, the results of the study concluded that students have good mastery of basic teaching skills, with an average score of 79%